76. Clinical Features and Burden of Post-Acute Sequelae of SARS-CoV-2 Infection in Children and Adolescents. (15th December 2022) - Rao, Suchitra; Lee, Grace; Lorman, Vitaly; Razzaghi, Hanieh; Mejias, Asuncion; Pajor, Nathan; Thacker, Deepika; Jhaveri, Ravi; Christakis, Dimitri; Webb, Ryan; Dickinson, Kimberley; Bailey, Charles; et al.
Abstract: Background: The post-acute sequelae of SARS-CoV-2 (PASC) has emerged as a long-term complication in adults, but current understanding of the clinical presentation of PASC in children is limited. Our study objectives were to identify symptoms, health conditions, and medications associated with PASC in children. Methods: We conducted a retrospective cohort study using electronic health records from 9 US children's hospitals for individuals < 21 years who underwent polymerase chain reaction (PCR) testing for SARS-CoV-2 between March 1, 2020 – October 31, 2021 and had at least 1 encounter in the 3 years before testing. Our exposure of interest was SARS-CoV-2 PCR positivity. We identified syndromic (symptoms), systemic (conditions), and medication PASC features in the 28–179 days following the initial test date. Adjusted hazard ratios (aHRs) were obtained for 151 clinically predicted PASC features by contrasting PCR-positive with PCR-negative groups using proportional hazards models, adjusting for site, age, sex, testing location, race/ethnicity, and time-period of cohort entrance. We estimated the incidence proportion for any syndromic, systemic or medication PASC feature in the two groups to estimate PASC burden. Results: Among 659, 286 children in the study sample, 59, 893 (9.1%) tested positive by PCR for SARS-CoV-2. Most were tested in outpatient testing facility (50.3%) or office (24.6%) settings (Table 1). The most common syndromic, systemic, and medication features were loss of taste or smell (aHR 1.96 [95% CI 1.16–3.32), myocarditis (aHR 3.10 [95% CI 1.94–4.96]) (Figures 1 and 2), and cough and cold preparations (aHR 1.52 [95% CI 1.18–1.96]). The incidence of at least one systemic/syndromic/medication feature of PASC was 42.0% among PCR-positive children versus 38.2% among PCR-negative children, with an incidence proportion difference of 3.8% (95% CI 3.3–4.3%). A higher strength of association for PASC was identified in those cared for in the ICU during the acute illness phase, children less than 5 years-old, and individuals with complex chronic conditions. Adjusted hazard ratios (aHR) with associated 95% CI among patients who tested positive for SARS-CoV-2 infection versus those who tested negative for the risk of each syndromic feature (symptom) using Cox proportional hazards models. Models were adjusted for age at cohort entrance, sex, race/ethnicity, institution, testing place location, presence of a complex medical condition and date of cohort entrance. Adjusted hazard ratios (aHR) with associated 95% CI among patients who tested positive for SARS-CoV-2 infection versus those who tested negative for the risk of each systemic feature using Cox proportional hazards models. Models were adjusted for age at cohort entrance, sex, race/ethnicity, institution, testing place location, and date of cohort entrance. For each health condition evaluated, patients with evidence of that condition 18 months before cohort entrance were excluded from the denominator in order to identify incident cases. Each ratio compares the risk of the outcome in children who tested positive for SARS-CoV-2 infection versus those who tested negative. Footnote: The diagnostic cluster for COVID-19 indicates children receiving care for the illness in the post-acute period. Conclusion: In this large-scale, exploratory study, the burden of PASC in children appeared to be lower than earlier reports. Acute illness severity, young age, and comorbid complex chronic disease increased the risk of PASC. Disclosures: Grace Lee, MD, MPH, United Health Group PASC Advisory Council: Advisor/Consultant Asuncion Mejias, MD, PhD, MsCS, Janssen: Advisor/Consultant|Janssen: Grant/Research Support|Merck: Advisor/Consultant|Merck: Grant/Research Support|Roche: Advisor/Consultant|Sanofi-Pasteur: Advisor/Consultant|Sanofi-Pasteur: Honoraria Ravi Jhaveri, MD, AstraZeneca: Advisor/Consultant|Dynavax: Advisor/Consultant|Elsevier: editorial stipend|Sequiris: Advisor/Consultant.